Renin-angiotensin system gene polymorphisms in children with Henoch—Schönlein purpura in West China - Desong Liu (Journal of the Renin-Angiotensin-Aldosterone System, 2010)
It has been suggested that renin-angiotensin system (RAS) gene polymorphism is involved in the pathogenesis of Henoch—Schönlein purpura (HSP) with conflicting reports. We therefore investigate the effect of RAS gene polymorphism on HSP susceptibility and severity in a Chinese cohort. The study included 142 children with HSP and 218 healthy controls that were genotyped for RAS gene polymorphisms. Significantly, differences of T174M-T and ACE-D frequency were found between HSP patients and controls ( p alleo = .002, OR alleo = 2.001; p alleo = .007, OR alleo = 1.533, respectively). We also found correlations between ACE-I/D and Agt T174M with multiple organ involvements, with significant differences in ACE-D in renal groups ( p < 0.05) and Agt T174M in non-renal ( p joint = .002, p GI = .042). Furthermore, decreasing M235T-T and increasing ACE-D were found associated with serious renal complications ( p = .019, p = .016). Additionally, ACE-I/D and T174M were significantly associated with high clinical score patients, as opposed to low clinical score patients, when patients were scored depending on the severity of overall complications ( p = .045, p = .026). We suggest that RAS gene polymorphisms ( ACE-I/D , M235T or T174M ) are significantly associated with susceptibility to HSP, organ involvement, and disease severity, which largely account for individual prognosis.